(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article discusses the issues of enhancing the intellectual potential of women in New Uzbekistan. Today, the movement of women in the process of scientific development and innovative development, increasing their socio-political activity is one of the important tasks in New Uzbekistan. In particular, the fact that women also have a special place in public administration, and the extremely wide range of achievements of women in various fields are pleasing.